THE PRESENT STATE OF THE COMPARATIVE STUDY OF RELIGIOUS ETHICS: An Update - Kelsay, John (Journal of religious ethics, 2012)
A survey of developments over the last forty years suggests that little progress has been made in the development of comparative religious ethics as a discipline. While authors working in this field have produced a number of interesting works, the field lacks structure, including an agreement on the basic purpose, terms, and approaches by which contributions may be evaluated as better or worse. I provide an account of this history, suggesting that a way forward will involve marrying ethicists' interest in arguments with close attention to the more and less formal structures by which groups of people organize the giving and taking of reasons.